Paradox of Discursive Integration: On Integrating Experiential Content Through Language - Marzęda, Witold (Folia Philosophica, 2021)
Theories of discursive integration form a group of theories that see the principles responsible for the integration of experience data (apperception) in the practices and schemes of discourse. These theories indicate that the use of language unites and organizes experience data. Their main assumption can be expressed as follows: this integration does not inhere in objects and cannot be derived from them; hence this integration cannot be secondarily expressed in language, but results exclusively from the use of language (or discourse). In this article, Witold Marzęda gives an overview of narrativist theories, script theories, Gazzaniga and Dennett’s models, which refer to evolutionary psychology, and the theories of Lakoff and Johnson – all these being theories of discursive integration. Marzęda’s main objective is to formulate a paradox, which consists in a trap of self-referentiality into which these theories fall: they postulate some general properties of discourse, which, firstly, do not have to become at once the properties of individual models and which, secondly, do not admit of falsification.